EFFECTIVENESS OF GROUP GUIDANCE WITH STRESS INOCULATION TRAINING TECHNIQUE IN REDUCING LEARNING BOREDOM - Pasaribu, Putri Dirgahayu; Lubis, Saiful Akhyar (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
The problem in this research is the high learning saturation of students, which hinders their ability to receive and understand lessons, leads to sleeping in class, a lack of enthusiasm for learning, and truancy. This study aims to determine the effectiveness of group guidance services using the stress inoculation training technique to reduce student learning saturation. This research employs a quantitative method with a one group pretest posttest design. The population in this study is 72 students from grade XII at state high school 10 Medan, with a sample of 10 students who have high learning saturation, selected using purposive sampling with a non-test instrument in the form of a questionnaire. The data analysis used is the Wilcoxon Signed Ranks Test with results showing that the asymp. Sig (2-tailed) significance value is less than () 0.05, which is an asymp. Sig (2-tailed) value of 0.003. The results obtained from the Wilcoxon signed rank test indicate that group counseling services using stress inoculation training techniques are effective in reducing students' learning boredom. The novelty of the research conducted by the researcher lies in the use of stress inoculation training techniques in the context of group counseling for students. Although stress inoculation training has been used in various therapeutic settings, its application in group counseling in schools is still rarely studied, and the situation after the findings indicate that students' learning boredom has decreased compared to before.